Sixth harmonic‐based fault location for VSC‐DC distribution systems. Issue 14 (21st July 2017) - Li, Meng; Jia, Ke; Bi, Tianshu; Yang, Qixun
Abstract : Accurate fault location methods are of major significance to the line maintenance of voltage source converter (VSC)‐DC distribution systems. However, power electronics change the fault‐characteristics, and the new fault theory is not fully mature. In addition, rapid fault isolation leaves little information for fault location. Fault location for VSC‐DC distribution systems is still a big challenge. The proposed fault location method is developed based on an equivalent feeding‐stage circuit derived herein. The line quantities sixth‐harmonics are used, and an improved discrete Fourier transform algorithm (IDFT) is proposed to remove the influence of both decaying periodic and DC components. Simulation results on PSCAD/EMTDC verified the feasibility of the proposed fault location and IDFT algorithms. Using local measurements with the sampling frequency of 9.6 kHz, the method can locate fault position within 10 ms and with less than 2% error.